A Rare Case with a Solitary Fibrous Tumour of the Colon and an Epithelioid Angiomyolipoma of the Kidney. (19th September 2013) - Pham, Thong Quang; Aida, Shinsuke; Mori, Ichiro; Koshida, Takeo; Ohigashi, Takashi; Katase, Katsuyoshi; Murakami, Fumiyoshi; Tran, Thong Minh; Osamura, Robert Y.
Abstract : Solitary fibrous tumour is a soft tissue tumour composed of a subset of fibroblast-like cells and frequently needs immunohistochemical staining for final diagnosis. Epithelioid angiomyolipoma is a variant of angiomyolipoma but characterized by the absence of both adipocytes and abnormal blood vessels. We introduce a very rare case with the combination of these two tumours. A Japanese female patient without significant symptom was hospitalized and operated due to multiple uterine leiomyomas. During the operation, the surgeons found another tumour attaching to serosa of sigmoid colon. This tumour was resected and interpreted as solitary fibrous tumour, suspicious of malignancy. After 13 months of treatment, she was hospitalized again due to hematuria. The doctors detected a tumour in her right kidney. After consultation, laparoscopic right nephrectomy was done. The pathological result of this tumour was epithelioid angiomyolipoma. This is the first report on this very rare combination of tumours with extensive immunohistochemical demonstration of both tumours. Hereby, we review clinical information and histopathological findings together with discussion on each tumour.